Verlagsgutachten und Nachworte. Zur Förderung und Zensierung deutscher Literatur in Polen nach 1945 - Orłowski, Hubert (Studia Germanica Posnaniensia, 2018)
The system of control and disciplining of Literature in the Polish People Republic distinguished in principal way from the system in German Democratic Republic. On the ground of the documents from the former Main Office for Press, Publications and Show-Control and from the authors private collection the mechanism of functioning of censorship and the trial to lead the readers interest were reconstructed. So called intern publishing opinions and afterwords create main field of authors interest. To demonstrate the mechanism of censorship and controll in a meaningfull way the mode for treating translations of prose written by Martin Walser and Christa Wolf was distinguished.